Australia’s Publicly Listed Manufacturing Companies – Analysing the connection between Return on Equity (ROE) and Altman Z-Scores - Pathak, Shaakalya; Liang, Foo See (Archives of Business Research, 2021)
Australia’s economy is considered to be a highly developed market economy and a reasonably large economy globally. This article seeks to analyse the connection between the business, or financial health, as measured by the Altman Z-Score, and corporate performance, as measured by the Return on Equity (ROE), of listed manufacturing companies in this market (the ASX or Australian Securities Exchange). A linear regression has been performed between these variables to ascertain the extent and direction of their relationships. The trends of Z-Scores over a five-year period have also been examined. The study covers the period from 2013 to 2017 (inclusive) and yields a statistically positive correlation between ROE and the Z-Score for the market. Australia registered moderate-to-strong mean and median Z-Scores. These findings further support the strong economic position of this market as a business giant.